Click to Chat

1800-2000-838

+91-120-4616500

CART 0

• 0

MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping
`              If x=cy+bz, y=az+cx, and z=bx+ay, show that x2/1-a2=y2/1-b2=z2/1-c2`
7 years ago

SHAIK AASIF AHAMED
74 Points
```										Hello student,Please find the answer to your question belowx = cy + bzy = az + cxy = az + c^2y + cb(1 - c^2)y = (a+bc)zmeanwhilez = bx + ayz = bcy + b^2z + ay(1 - b^2)z = (a + bc)yfrom first set:y/(a+bc) = z/(1 - c^2)(a + bc)y/(1 - b^2) = zmultiply left equation to left.. and right equation to right equation also .y^2/(1 - b^2) = z^2/(1 - c^2)then you can continue with the rest of the equation
```
3 years ago
SHAIK AASIF AHAMED
74 Points
```										Hello student,Please find the answer to your question belowx = cy + bzy = az + cxy = az + c^2y + cb (1 - c^2)y = (a+bc)zmeanwhile z = bx + ay z = bcy + b^2z + ay (1 - b^2)z = (a + bc)yfrom first set: y/(a+bc) = z/(1 - c^2)(a + bc)y/(1 - b^2) = z multiply left equation to left.. and right equation to right equation also . y^2/(1 - b^2) = z^2/(1 - c^2) then you can continue with the rest of the equation
```
3 years ago
Think You Can Provide A Better Answer ?

## Other Related Questions on Algebra

View all Questions »
• Complete JEE Main/Advanced Course and Test Series
• OFFERED PRICE: Rs. 15,900
• View Details

Post Question